2006
DOI: 10.1097/01.bcr.0000200910.76019.cf
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Using Dexmedetomidine in Pediatric Burn Patients

Abstract: Maintaining appropriate sedation and analgesia in pediatric burn patients can be quite challenging and often requires high doses of analgesics and anxiolytics because tolerance quickly develops. Escalating doses of opioids and benzodiazepines provide little additional benefit while increasing the incidence of side effects. Dexmedetomidine (DEX) is a novel alpha2-adrenergic agonist that provides sedation, anxiolysis, and analgesia with much less respiratory depression than other sedatives. In addition, DEX stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 16 publications
2
67
0
1
Order By: Relevance
“…This result contradicts earlier findings in smaller pediatric critical care studies, which indicated that dexmedetomidine was associated with adequate sedation in greater than 90% of cases. 3,24,27 However, investigators in previous studies used different methods of evaluating sedation, for example, using alternative evaluation tools or counting the number of rescue bolus doses. In addition, lack of familiarity with dexmedetomidine, especially immediately after its addition to the hospital formulary, may have led to less than optimal use.…”
Section: Discussionmentioning
confidence: 99%
“…This result contradicts earlier findings in smaller pediatric critical care studies, which indicated that dexmedetomidine was associated with adequate sedation in greater than 90% of cases. 3,24,27 However, investigators in previous studies used different methods of evaluating sedation, for example, using alternative evaluation tools or counting the number of rescue bolus doses. In addition, lack of familiarity with dexmedetomidine, especially immediately after its addition to the hospital formulary, may have led to less than optimal use.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended for short-term use only, less than 48 h. Minimal efficacy, pharmacokinetic, and safety data exist for neonates. Despite limited testing and without current Food and Drug Administration approval, the off-label use of DEX in pediatric and neonatal intensive care units is increasing (10)(11)(12). Since DEX can provide sedation and prevent shivering, it is a viable alternative to opioids for neonatal intensive care units patients undergoing therapeutic hypothermia as treatment for HIE.…”
mentioning
confidence: 99%
“…Owens et al [6] in their study found that 2.9% of the patients who received ketamine during sedation experienced side effects such as desaturation, apnoea, hypotension. Walker et al [23] found that no respiratory depression associated with the use of dexmedetomidine had occurred. Taghinia et al [24] also reported that dexmedetomidine decreases the frequency of oxygen desaturation and reduces the amounts of narcotic and anxiolytic requirement.…”
Section: Discussionmentioning
confidence: 99%